Our town, a play in three acts (Perennial classic, ,, 1965)
This beautiful new edition features an eye-opening Afterword written by Tappan Wilder that includes Thornton Wilder's unpublished notes and other illuminating photographs and documentary material. Our Town was first produced and published in 1938 to wide acclaim. This Pulitzer Prize-winning drama of life in the small village of Grover's Corners, an allegorical representation of all life, has become a classic. It is Thornton Wilder's most renowned and most frequently performed play.

Brave new world (Classic ed, ,, 2008)
Towering classic of dystopian satire, BRAVE NEW WORLD is a brilliant and terrifying vision of a soulless society--and of one man who discovers the human costs of mindless conformity. Hundreds of years in the future, the World Controllers have created an ideal civilization. Its members, shaped by genetic engineering and behavioral conditioning, are productive and content in roles they have been assigned at conception. Government-sanctioned drugs and recreational sex ensure that everyone is a happy, unquestioning consumer; messy emotions have been anesthetized and private attachments are considered obscene. Only Bernard Marx is discontented, developing an unnatural desire for solitude and a distaste for compulsory promiscuity. When he brings back a young man from one of the few remaining Savage Reservations, where the old unenlightened ways still continue, he unleashes a dramatic clash of cultures that will force him to consider whether freedom, dignity, and individuality are worth suffering for.

The art of loving (World perspectives, 9,, 2006)
"Presents his view of the nature of love involving the whole personality and an orientation toward life." --
I. Is love an art? , II. The theory of love. Love, the answer to the problem of human existence , Love between parent and child , The objects of love : Brotherly love ; Motherly love ; Erotic love ; Self-love ; Love of God , III. Love and its disintegration in contemporary Western society , IV. The practice of love.

V (Harper Perennial modern classics, ,, 1963)
Having just been released from the Navy, Benny Profane is content to lead a slothful existence with his friends, where the only real ambition is to perfect the art of "schlemihlhood," or being a dupe, and where "responsibility" is a dirty word. Among his pals--called the Whole Sick Crew--is Slab, an artist who can't seem to paint anything other than cheese danishes. But Profane's life changes dramatically when he befriends Stencil, an active ambitious young man with an intriguing mission--to find out the identity of a woman named V [Victoria Wren], who knew Stencil's father during the war, but who suddenly and mysteriously disappeared

House made of dawn (Recorded Books classics library, ,, 2018)
House Made of Dawn, which won the Pulitzer Prize in 1969, tells the story of a young American Indian named Abel, home from a foreign war and caught between two worlds: one his father's, wedding him to the rhythm of the seasons and the harsh beauty of the land; the other of industrial America, a goading him into a compulsive cycle of dissipation and disgust.

Mules and men (Harper Perennial modern classics, ,, 2009)
Mules and Men is a treasury of black America's folklore as collected by a famous storyteller and anthropologist who grew up hearing the songs and sermons, sayings and tall tales that have formed an oral history of the South since the time of slavery. Returning to her hometown of Eatonville, Florida, to gather material, Zora Neale Hurston recalls "a hilarious night with a pinch of everything social mixed with the storytelling." Set intimately within the social context of black life, the stories, "big old lies," songs, Vodou customs, and superstitions recorded in these pages capture the imagination and bring back to life the humor and wisdom that is the unique heritage of African Americans. -- Publisher's website.
Folk tales , Hoodoo , Glossary , Appendix: I. Negro songs with music ; II. Formulae of Hoodoo doctors ; III. Paraphernalia of conjure ; IV. : Prescriptions of root doctors , Chronology , In search of Zora Neale Hurston / Alice Walker , Wrestling with Mules and men : the story behind the book.

Zen and the art of motorcycle maintenance: an inquiry into values (Harper Perennial modern classics, ,, 2009)
Acclaimed as one of the most exciting books in the history of American letters, this modern epic became an instant bestseller upon publication in 1974, transforming a generation and continuing to inspire millions. A narration of a summer motorcycle trip undertaken by a father and his son, the book becomes a personal and philosophical odyssey into fundamental questions of how to live. The narrator's relationship with his son leads to a powerful self-reckoning the craft of motorcycle maintenance leads to an austerely beautiful process for reconciling science, religion, and humanism. Resonant with the confusions of existence, Zen and the Art of Motorcycle Maintenance is a touching and transcendent book of life.

The monkey wrench gang (Harper Perennial modern classics, ,, 1975)
Ex-Green Beret George Hayduke returns from war to find his beloved southwestern desert threatened by industrial development. Joining with Bronx exile and feminist saboteur Bonnie Abzug, wilderness guide and outcast Mormon Seldom Seen Smith, and libertarian billboard torcher Doc Sarvis, M.D., Hayduke is ready to fight the power. They (the Monkey Wrench Gang) take on the strip miners, clear-cutters, and the highway, dam, and bridge builders who are threatening the natural habitat in this is a comedic novel of destructive mayhem and outrageous civil disobedience.

Under the volcano (Harper Perennial modern classics, ,, 2009)
"Geoffrey Firmin, a former British consul, has come to Quauhnahuac, Mexico. His debilitating malaise is drinking ... On ... the Day of the Dead, 1938, his wife, Yvonne, arrives in Quauhnahuac, inspired by a vision of life together away from Mexico and the circumstances that have driven their relationship to the brink of collapse. She is determined to rescue Firmin and their failing marriage, but her mission is further complicated by the presence of Hugh, the consul's half brother, and Jacques, a childhood friend ..."--Page [4] of cover of Harper Perennial Modern Classics ed.

Pilgrim at Tinker Creek (Harper Perennial Modern Classics, ,, 2009)
This work, a collection of essays on the natural world during a year spent in the Blue Ridge valley of Virginia, reflects the author's interactions with her wilderness surroundings. The author takes us through a year of on-foot explorations through her own landscape, bringing anecdotes, curiosities, and insights about all she observes and experiences. In the summer, she stalks muskrats in the creek and thinks about wave mechanics; in the fall, she watches a monarch butterfly migration and dreams of Arctic caribou. She tries to con a coot, unties a snakeskin, witnesses a flood, and plays "King of the Meadow" with a field of grasshoppers. It is an exploration into the nature of Nature, an attempt to discover the true character of the natural world around us.
1. Heaven and earth in jest , 2. Seeing , 3. Winter , 4. The fixed , 5. Untying the knot , 6. The present , 7. Spring , 8. Intricacy , 9. Flood , 10. Fecundity , 11. Stalking , 12. Nightwatch , 13. The horns of the altar , 14. Northing , 15. The waters of separation.

Tao te ching: a new English version (Harper Perennial modern classics, ,, 2006)
Printed throughout in two colors is this new, definitive version of one of the great books of world literature--comparable in its sales and influence to the Bible, the Bhagavad Ghita, and the Koran.
The Problem of Authorship --, The Nature of the Work.

A people's history of the United States (Harper Perennial modern classics, ,, 2009)
Presents the history of the United States from the point of view of those who were exploited in the name of American progress.
Vol. 1. American beginnings to Reconstruction , Vol. 2. The Civil War to the present.

A short history of Reconstruction, 1863-1877 (Harper Perennial modern classics, ,, 2015)
Looks at the social, economic, and political forces that shaped the South after the Civil War.
The world the war made , Rehearsals for Reconstruction , The meaning of freedom , Ambiguities of free labor , The failure of presidential Reconstruction , The making of radical Reconstruction , Blueprints for a republican South , Reconstruction : political and economic , The challenge of enforcement , The Reconstruction of the North , The politics of depression , Redemption and after.

Tell my horse: voodoo and life in Haiti and Jamaica (Harper Perennial modern classics, ,, 2009)
The author recounts her experiences as an initiate into the voodoo practices of Haiti and Jamaica in the 1930s.
Pt. I. Jamaica. The rooster's nest , Curry goat , Hunting the wild hog , Night song after death , Women in the Caribbean , pt. II. Politics and personalities of Haiti. Rebirth of a nation , The next hundred years , The black Joan of Arc , Death of Leconte , pt. III. Voodoo in Haiti. Voodoo and voodoo gods , Isle de la Gonave , Archahaie and what it means , Zombies , Secte rouge , Parlay cheval ou (tell my horse) , Graveyard dirt and other poisons , Doctor Reser , God and the Pintards , Appendix. Songs of worship to voodoo gods , Miscellaneous songs.

Black boy: (American hunger) : a record of childhood and youth (Harper Perennial modern classics, ,, 1998)
"The autobiography of an African-American writer, recounting his early years and the harrowing experiences he encountered drifting from Natchez to Chicago to Brooklyn."--

Letters from the earth: uncensored writings (Harper Perennial modern classics, ,, 2009)
Foreword / by Henry Nash Smith. -- Letters from the Earth. -- Papers of the Adam family: Extract from Methuselah's diary ; A later extract from Methuselah's diary ; Extract from Eve's autobiography ; Passage from Eve's autobiography ; The world in the year 920 after creation ; Two fragments from a suppressed book called "Glances at history" or "Outlines of history" ; Extract from Shem's diary of 920 A.C. -- Letter to the Earth. -- A cat-tale. -- Cooper's prose style. -- Official report to the I.I.A.S. -- The Gorky incident. -- Simplified spelling. -- Something about repentance. -- From an English notebook: The Albert Memorial ; Old Saint Paul's ; The British Museum. -- From the manuscript of "A tramp abroad": the French and the Comanches. -- From an unfinished burlesque of books on etiquette: At the funeral ; At a fire ; Visiting cards. -- The damned human race: Was the world made for man? ; In the animals' court ; Zola's La terre ; The intelligence of God ; The lowest animal. -- The great dark.
Foreword / by Henry Nash Smith. , Letters from the Earth. , Papers of the Adam family: Extract from Methuselah's diary ; A later extract from Methuselah's diary ; Extract from Eve's autobiography ; Passage from Eve's autobiography ; The world in the year 920 after creation ; Two fragments from a suppressed book called "Glances at history" or "Outlines of history" ; Extract from Shem's diary of 920 A.C. , Letter to the Earth. , A cat-tale. , Cooper's prose style. , Official report to the I.I.A.S. , The Gorky incident. , Simplified spelling. , Something about repentance. , From an English notebook: The Albert Memorial ; Old Saint Paul's ; The British Museum. , From the manuscript of "A tramp abroad": the French and the Comanches. , From an unfinished burlesque of books on etiquette: At the funeral ; At a fire ; Visiting cards. , The damned human race: Was the world made for man? ; In the animals' court ; Zola's La terre ; The intelligence of God ; The lowest animal. , The great dark.

Three plays: Our town, the Skin of Our Teeth, the Matchmaker ; [with a new foreword by John Guare] (Harper Perennial modern classics, ,, 2006)
This important new omnibus edition features an illuminating foreword by playwright John Guare and an extensive afterword for each play drawing on unpublished letters and other unique documentary material prepared by Tappan Wilder. Our Town: Wilder's timeless 1938 Pulitzer Prize-winning look at love, death, and destiny is celebrated around the world and performed at least once each day in the United States. The Skin of our Teeth: Wilder's 1942 romp about human follies and human endurance starring the Antrobus family of Excelsior, New Jersey. Winner of the Pulitzer Prize for Drama in 1943. The Matchmaker: Wilder's brilliant 1954 farce about money and love starring that irrepressible busybody Dolly Gallagher Levi. This play inspired the Broadway musical Hello, Dolly! - Publisher.
Our town , The skin of our teeth , The matchmaker.

The web and the root: a selection from The web and the rock (Harper Perennial modern classics, ,, 2009)
"The Web and the Root features the three initial sections of the The Web and the Rock, widely considered to be the book's strongest material. A prequel to You Can't Go Home Again, it is the story of George Webber's momentous journey from Libya Falls, North Carolina, to the Golden City of the North--offering vivid, sometimes cutting depictions of rural pleasures and small-town clannishness while exploring boundless urban possibility and the complex, violent undercurrents of the metropolis"--P. [4] of cover.
Book I. The web and the root. The child Caliban ; Three o'clock ; Two worlds discrete ; The golden city --, Book II. The hound of darkness. Aunt Mag and Uncle Mark ; The street of the day ; The butcher ; The child by tiger ; Home from the mountain --, Book III. The web and the world. Olympus in Catawba ; The priestly one ; The torch ; The rock ; The city patriots ; Götterdämmerung ; Alone.